Magnetic nanoparticles: Co@SiO2, Co@Au and Co@Pt - Sargentelli, Vagner; Ferreira, Antônio Aparecido Pupim (Eclética Química, 2014)
Nanotechnology is the understanding and control f matter at dimensions of roughly 1 – 100 nm. At the nanoscale, the properties like electrical conductivity and mechanical strength are not the same as the materials with particles in dimensions much more than 100 nm. The electronic structure changes dramatically too. Between nanomate-rials, there is recently a great number of works that investing as the synthesis as the properties of the magnetic nanoparticles. Some of more representative magnetic materials are the metallic oxides, as some ferrites. However, the ferrites are often obtained as mixture of some oxides, which implies that the magnetic properties are not always well defined and reproducible. Thus, the research has been turned to use of the magnetic metals, between which the cobalt. The cobalt is investigated because its high magnetic susceptility. However, this transition metal is easily oxidized in air and is toxic to human organism. For this reason, it has looked for to effect synthesis involving core – shell structures, as of silica and of gold: Co@SiO2, Co@Au and Co@Pt.